Handheld X-ray Fluorescence Spectrometers: A Forensic Application in Cigarette Ashes - Beatriz P. Senra; Helena Ribeiro; Alexandra Guedes (RevSALUS, 2025)
Background: Handheld X-ray fluorescence (HHXRF) technology has been increasingly applied for inorganic elemental characterization in many fields of science, offering a rapid, low-cost, multi-element analysis. Also, this equipment can perform non-invasive analysis, thus representing the most environmentally friendly approach. Objective:  The main objective of this study is to test the capability of HHXRF to analyze the elemental concentration of individual cigarette ash of several tobacco brands and investigate if it is further possible to discriminate the different brands based on their ash’s elemental concentration. Methods: A survey was made to a Portuguese target audience with an estimated age between 18 and 55 years to evaluate Portugal's ten most smoked tobacco brands and models. A numerical code from B1 to B10 was created to replace the brand names and models of the tobacco packs used.  To conduct a test for comparing two packs of tobacco of the same brand, another pack of the most smoked brand was purchased in the same store. For smoking the cigarettes a specially designed equipment of the Borgwaldt brand, model RM1/Plus, was used. For a more representative sample from each pack, five cigarettes per pack were smoked and each cigarette ash was measured five times, giving a total of 55 cigarettes smoked from 10 different brands (11 different tobacco packs). For the inorganic quantification of cigarette ash, an Oxford Instruments Handheld XRF spectrometer, model X-MET7500 was used. The elements present in cigarette ashes and included in this study were 14: Al (aluminum), Ca (calcium), Cl (chlorine), Cu (copper), Fe (iron), K (potassium), Mn (manganese), P (phosphorus), Rb (rubidium), S (sulfur), Si (silicon), Sr (strontium), Ti (titanium) and Zn (zinc), because were those found in greatest concentration and therefore allow for more robust analysis and comparison. The statistical analysis of the data retrieved from the ash inorganic elemental analysis was done using the IBM SPSS Statistics program. Results: The elements with the most variable concentrations are Al, Cl, Fe and Si. In comparison between brands, the grouping joined the most similar brands based on their ash elemental concentrations. The first one represents brands with higher overall concentrations of elements compared to the other group brands. In comparison between cigarettes, for the elements P, S, Cl, K and Ca, it is possible to see that their concentrations vary significantly among cigarettes of the same brands. These elements are considered micronutrients in the plants, in this case, the tobacco plant [1,2], and therefore can result in greater variability among the various batches produced. However, it is possible to state that there are four brands whose five cigarettes are grouped. This tells us that the intra-brand variation is insufficient to nullify the inter-brand difference. Conclusions: This study reveals the capability of handheld X-ray fluorescence to discriminate tobacco brands based on their ashes' elemental concentration, with a major advantage of the analyses being non-destructive and not requiring a large sample. In addition, this equipment can measure the ash's elemental concentrations on-site, allowing for less contamination and sample loss [3].